Dynamics of periodic modes for the phenomenological equation of spin combustion - Belan, E. P.; Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We consider a scalar parabolic equation in the circle of radius r. This problem is a gasless combustion phenomenological model in the surface of a cylinder of r radius. We consider the problems of the existence, asymptotic form and stability of traveling waves and the nature of gaining, losing their stability.